2021
DOI: 10.1021/acsestwater.0c00255
|View full text |Cite
|
Sign up to set email alerts
|

Ferrate(VI) Oxidation of Pharmaceuticals in Hydrolyzed Urine: Enhancement by Creatinine and the Role of Fe(IV)

Abstract: Treatment of human urine is an emerging approach to minimize environmental pharmaceutical contamination. This study investigated the application of ferrate(VI) (Fe VI O 4 2−, Fe(VI)) oxidation to degrade pharmaceuticals (i.e., carbamazepine (CBZ), naproxen (NAP), sulfamethoxazole (SMX), and trimethoprim (TMP)) in synthetic hydrolyzed human urine, with the emphasis on the effects of urine endogenous organic metabolites. Creatine and hippuric acid showed limited to moderate scavenging effects. Creatinine (CRE) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 70 publications
(102 reference statements)
1
36
0
Order By: Relevance
“…The amines in surface water are present in the form of dissolved organic nitrogen from wastewater discharges, algal blooms, and agricultural runoff activities. Amines as co-contaminants with pharmaceuticals would enhance and accelerate the oxidation of the target contaminants by Fe­(VI), for example, the enhanced efficiency of the oxidation of pharmaceuticals in the presence of creatinine in hydrolyzed urine . However, this effect of amines depends on the concentration of amines compared to that of Fe­(VI) because the formation of the Fe IV –amine complex and its enhanced performance depend on the molar ratio of amine to Fe­(VI).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amines in surface water are present in the form of dissolved organic nitrogen from wastewater discharges, algal blooms, and agricultural runoff activities. Amines as co-contaminants with pharmaceuticals would enhance and accelerate the oxidation of the target contaminants by Fe­(VI), for example, the enhanced efficiency of the oxidation of pharmaceuticals in the presence of creatinine in hydrolyzed urine . However, this effect of amines depends on the concentration of amines compared to that of Fe­(VI) because the formation of the Fe IV –amine complex and its enhanced performance depend on the molar ratio of amine to Fe­(VI).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of oxidation of pollutants, including amine-containing molecules, by Fe­(VI) possibly involves iron­(IV) (Fe IV ), iron­(V) (Fe V ), or both as the intermediate(s). In the past, the complexation of ammonia with Fe IV and Fe V has been proposed to describe the observed results for the oxidation of ammonia by Fe­(VI). , Recently, we have found that creatinine (2-amino-1-methyl-5 H -imidazol-4-one, CRE), an amine-containing major organic constituent of urine, could enhance the degradation of pharmaceuticals by Fe(VI) . CRE is known to be a ligand for metal ions, including iron .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Inadequate disposal of expired medicines via toilets, trash, or drains is also a major source of pharmaceutical pollution. 5 The complex structure of these ingredients makes wastewater toxic, persistent, and complex. 6 Bulk drug pharmaceuticals include various types of chemical substances, such as antibiotics, analgesics, and antiinflammatories, that are used to treat various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of emerging contaminants, including pharmaceuticals, in the aquatic system has become a global issue because of their harmful effects on aquatic life and physiological effects on humans. , Pharmaceutical compounds enter the aquatic environment either directly from the production plant or indirectly through anthropogenic activities such as sewage discharge, breeding, and landfill leachate, which results in their presence in groundwater and surface water. , Inadequate disposal of expired medicines via toilets, trash, or drains is also a major source of pharmaceutical pollution . The complex structure of these ingredients makes wastewater toxic, persistent, and complex .…”
Section: Introductionmentioning
confidence: 99%